2024
DOI: 10.3390/jcdd11020044
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein B and Lipid Profile in Italian Children and Adolescents

Francesco Martino,
Tarcisio Niglio,
Eliana Martino
et al.

Abstract: Rationale. The prevention of cardiovascular (CV) disease is mandatory from childhood onwards. Among biochemical markers related to the clinical cardiovascular outcome, LDL cholesterol (LDL-C), non-HDL-C and apolipoprotein B (ApoB) are recognized as main target parameters. Emphasis on ApoB concentrations is growing, as representative of any class of atherogenic lipoprotein. This consideration allows checking of subjects under 18 years of age when the CV risk occurs. The aim of this study is to evaluate ApoB lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The prevalence of dyslipidaemias is increasing all over the world, even in Mediterranean countries where the diet should be qualitatively healthier. A recent Italian study showed a prevalence of suboptimal cholesterolemia (total cholesterol-TC > 170 mg/dL) in 78% of children and adolescents [3]. Recent studies suggest that long-term mild exposure during childhood to even a mild suboptimal LDL-C level is associated with an increased risk of coronary artery disease.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of dyslipidaemias is increasing all over the world, even in Mediterranean countries where the diet should be qualitatively healthier. A recent Italian study showed a prevalence of suboptimal cholesterolemia (total cholesterol-TC > 170 mg/dL) in 78% of children and adolescents [3]. Recent studies suggest that long-term mild exposure during childhood to even a mild suboptimal LDL-C level is associated with an increased risk of coronary artery disease.…”
Section: Introductionmentioning
confidence: 99%